Analisis Corak Pemikiran Masyarakat Dalam Melaksanakan Sedekah Jumat Berkah - Yuhaswita Yuhaswita; Imam Mahdi; Moch. Iqbal; Fatihatur Rahmi Azizah (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2024)
The Friday blessings charity movement has gained popularity and is being actively discussed and practiced by the community some years after the Covid-19 era. The community is competing to carry out Friday blessings charity, which is a manifestation of the community's concern for those in dire need of assistance to fulfill their food needs. The purpose of this study is to analyze the Friday Blessing charity activities using an Islamic Theology approach. The research method employed in this study is qualitative descriptive research, namely a literature review. The sources of data include journals and books on Islamic theology. The research findings reveal that the act of giving Friday alms is considered a virtuous deed due to its concern for fellow human beings. According to Islamic theology, those who engage in Friday alms have utilized their intellect to contemplate both good and evil. Furthermore, individuals who participate in the act of giving Friday alms are considered to be believers in their heart, speech, and actions. The community that has engaged in the blessed Friday activities is a community that thinks rationally, similar to the Mu'tazilah and Qadariyah schools of thought.